2016
DOI: 10.1016/j.otsr.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of preoperative determinants of patient-reported pain and physical function up to 2 years following primary unilateral total hip arthroplasty

Abstract: Level II. Systematic review of cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…The first was in relation to baseline function/disability with the majority of studies showing that worse baseline function predicted poor outcome, this was however not the case when studies looked at change scores rather than purely follow‐up outcome, for example Hofstede et al () found that a lower functional PROM score (indicating lower function) predicted worse outcome conforming to other studies but also to greater improvement (change). This was also found by Harmelink et al (), and Lungu, Maftoon, Vendittoli, and Desmeules (), Lungu, Vendittoli, and Desmeules (). This shows that patients with lower functional scores achieve a better outcome with regard to health gain but still a worse overall outcome than those with higher baseline scores in relation to follow‐up functional PROM scores achieved.…”
Section: Discussionsupporting
confidence: 81%
“…The first was in relation to baseline function/disability with the majority of studies showing that worse baseline function predicted poor outcome, this was however not the case when studies looked at change scores rather than purely follow‐up outcome, for example Hofstede et al () found that a lower functional PROM score (indicating lower function) predicted worse outcome conforming to other studies but also to greater improvement (change). This was also found by Harmelink et al (), and Lungu, Maftoon, Vendittoli, and Desmeules (), Lungu, Vendittoli, and Desmeules (). This shows that patients with lower functional scores achieve a better outcome with regard to health gain but still a worse overall outcome than those with higher baseline scores in relation to follow‐up functional PROM scores achieved.…”
Section: Discussionsupporting
confidence: 81%
“…However, Lungu et al. (2016) did not find any significant association between age and outcomes after THA. In our hospital, there is selection of patients who are to be operated in an outpatient setting, and they must fulfill the following criteria: ASA I or II; being motivated to go home on the day of surgery; having no cardiovascular history; not having insulin-dependent diabetes; and having sufficient support from a caring person at home during the first night postoperatively (Hartog et al.…”
Section: Discussionmentioning
confidence: 85%
“…Lungu et al. (2016) found that a greater level of comorbidity and worse general health are associated with worse pain and function following THA.…”
Section: Discussionmentioning
confidence: 99%
“…Although hip and knee replacement are performed to reduce pain and regain function in patients with late-stage arthritis [1,2], 10-20% of patients continue to suffer from persistent pain after surgery [3,4]. The latest studies focusing on persistent pain indicate that its major risk factors include pain catastrophizing, intensity of preoperative pain, mental health problems, knee surgery, and certain comorbidities, such as diabetes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%